An Integrated Islamic Edupreneurship Model for the Economic Independence of Islamic Educational Institutions - Finka Oktaviana Putri; Lidia Astuti; Muhammad Sidiq Purnomo; Adi Nur Ali (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to develop an Integrated Islamic Edupreneurship Model (IIEM) explaining how Islamic spiritual values, creativity, innovation, and edupreneurship interact to strengthen the economic independence of Islamic educational institutions without compromising their educational, religious, and social missions. An integrative literature review was conducted using 56 publications retrieved from Scopus, Web of Science, Google Scholar, and Garuda, covering studies published between January 2015 and July 2026, while retaining seminal earlier works. The literature was critically evaluated and analyzed through qualitative content analysis, deductive and inductive coding, thematic synthesis, cross-study comparison, and conceptual integration. The findings indicate that economic independence cannot be achieved merely through revenue growth or business-unit development. Instead, it emerges from a value-governed process in which tawhid establishes institutional purpose, amanah reinforces accountability, siddiq ensures truthfulness, ihsan promotes excellence, and maslahah directs activities toward educational and social benefit. These values guide creativity in generating contextually relevant ideas, innovation in implementing and institutionalizing those ideas, and edupreneurship in organizing productive activities, partnerships, digital services, and resource mobilization. It also identifies leadership, organizational capacity, and stakeholder participation as important contextual conditions. The originality of IIEM lies in positioning spiritual values as an active governance mechanism rather than an ethical addition, while distinguishing creativity as idea generation, innovation as implementation, edupreneurship as an institutional mechanism, and economic independence as a multidimensional outcome. The study contributes a dynamic framework incorporating feedback, mission protection, stakeholder accountability, and balanced financial, educational, ethical, and social performance indicators. It provides a theoretical basis for future empirical validation and practical guidance for Islamic educational institutions seeking diversified income, institutional resilience, improved educational quality, and sustainable community welfare.